The research of human individual's conformity behavior in emergency situations. Issue 3 (31 December 0018) - Chen, Min
Abstract : Purpose: The purpose of this paper (including three studies) is to investigate the idea that individuals in an emergency situation experience significantly a higher level of emotional activation, lower performance of task, and change in decision making, escaping behavior and conformity as compared to being in a non-emergency situation. It is also suggested that the level of emotional activation mediates the association between situation and the performance of task. Design/methodology/approach: Study 1 was an experimental study with 43 university students and revealed that different situations induced different levels of emotional activation and they are positively and significantly related. Study 2 was a further exploration of study 1, in which 49 participants were asked to watch a recomposed video telling a reasonable story about escaping from the emergency and complete several tasks associated with two kinds of situations (non-emergency vs emergency). In study 3, 168 participants, randomly assigned to three groups, were asked to work on judgment tasks with different numbers of options. Findings: Results revealed that individuals in an emergency situation experience significantly lower performance of task and higher conformity tendency than in a non-emergency situation. Also, the causal effect of the situation on the performance of task is mediated by the level of emotional activation. Moreover, results found that the performance of task is also a mediator between the level of emotional activation and conformity. Result showed that the number of choices is negatively related to conformity, and performance is a mediator between the number of choices and conformity. Originality/value: This paper suggested that the level of emotional activation mediates the association between situation and the performance of task.